The casualty profile from the Manchester bombing 1996: a proposal for the construction and dissemination of casualty profiles from major incidents. Issue 2 (March 1997) - Carley, S D; Mackway-Jones, K
Abstract : OBJECTIVE: To produce a casualty profile for the Manchester bombing and to illustrate the potential uses of such templates in major incident planning. METHODS: A retrospective review of casualty notes from the Manchester bombing. RESULTS: A complete anonymous casualty profile for the Manchester bombing is given with AIS90 coded injuries. The majority (129, 62%) of casualties sustained minor injuries from flying glass. A significant number of casualties (36, 18%) presented with emotional distress or medical problems. A wide age range of casualties was involved. Few patients (19, 9%) required admission to hospital. There were no deaths and no casualties sustained major trauma. CONCLUSIONS: Casualty profiles may be useful in the planning and testing of health service major incident plans. Such information should be easily accessible to all emergency planners.